ANALISIS STRUKTUR KUDA-KUDA BAJA RINGAN DI PERUMAHAN GRAHA PERMATA KOTA - , AGUNG WAHYU UTOMO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The profiles of Cold Formed steel have advantages such as force structure in a stronger, lighter, environmentally friendly, easy in implementation / assembly, does not propagate fire, precision in size, not a lot of wasted material, and can be recycled. The purpose of this study to determine the strength of the structure cold formed steel truss in graha permata kota The results of the study are regulation (SNI 03-1729-2002) can not be applied to cold formed steel because it has a much value ratio. And review of regulations that can be used for Cold formed steel is the Australian New Zealand Standard Cold Formed Steel Structures (AS / NZS 4600:2005)